Introducing Midwifery-led Birth Centres to Ontario - Cristina A. Mattison (Health Reform Observer - Observatoire des Réformes de Santé, 2015)
In Ontario, maternal health systems are changing, with an increasing variety of childbirth options being offered to low-risk pregnant women. Midwifery became a regulated profession in the province in 1994: providing primary care throughout pregnancy, labour and for up to six weeks postpartum. Currently there are three midwifery-led birth centres operating in Ontario, two of which opened in early 2014. The Ministry of Health and Long-Term Care (MoHLTC) has launched these new birth centres in order to offer women more choice in health care provider and birth setting. This shift is representative of the MoHLTC’s push to move services out of hospitals and into community-based settings. While the birth centre initiative is in its early stages and a formal program evaluation is needed, it has the potential, if scaled up, to decrease the need for hospital beds as well as reduce health care costs through more appropriate care for low-risk pregnancies, leading to fewer interventions.